2021
DOI: 10.1002/14651858.cd013700.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for gastrointestinal and pancreatic neuroendocrine tumours: a network meta-analysis

Abstract: Treatment for gastrointestinal and pancreatic neuroendocrine tumours: a network meta-analysis (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…High-risk features include, in particular, deep mid-appendiceal invasion >3 mm, positive lymphovascular/vascular invasion, positive or indistinct cut margins, and high proliferation rates [ 19 ]. Over the last 10 years, many treatment options have been developed for metastatic aNETs, including pharmacological treatment with targeted drugs, cytotoxic chemotherapy or somatostatin, and external beam radiotherapy [ 5 , 20 , 21 ]. Long-acting somatostatin analogues were effective in inhibiting tumor growth in randomized phase III trials (CLAIRNET and PROMID) and are used to treat metastatic, well-differentiated aNETs [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…High-risk features include, in particular, deep mid-appendiceal invasion >3 mm, positive lymphovascular/vascular invasion, positive or indistinct cut margins, and high proliferation rates [ 19 ]. Over the last 10 years, many treatment options have been developed for metastatic aNETs, including pharmacological treatment with targeted drugs, cytotoxic chemotherapy or somatostatin, and external beam radiotherapy [ 5 , 20 , 21 ]. Long-acting somatostatin analogues were effective in inhibiting tumor growth in randomized phase III trials (CLAIRNET and PROMID) and are used to treat metastatic, well-differentiated aNETs [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three small randomized trials comparing SSA vs SSA plus interferon-alpha (IFNα) showed some advantage for the combination but could not detect a statistically significant OS benefit ( Fazio et al 2007 ), while two recent network meta-analyses confirmed the efficacy of SSA plus IFNα in non-pancreatic NET ( Kaderli et al 2019 , Walter et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%